PENGARUH BRAND IMAGE DAN COUNTRY OF ORIGIN TERHADAP MINAT BELI KONSUMEN PRODUK HANDPHONE MEREK ASUS (Survei Konsumen Pada Pusat Penjualan Asia Ponsel Center Pekanbaru) - Suri, Atika; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine the effect of Brand Image and Country Of Origin on consumer purchase Interest on Asus Handphone Products (Consumer Survey At Asia Ponsel Center Pekanbaru). The Brand image as a variable (X1), Country of origin as variable (X2) and Consumer purchase interest as variable (Y). Brand Image is one important part in the company because the attitude and actions of consumers against a company brand is determined by the brand image of the company. Country Of Origin is a person's view of a product from the country of origin of the product concerned.This research was conducted at Asia Ponsel Center Pekanbaru and took the number of respondents ie 100 people. The data from the questionnaire is further processed using statistical analysis that is simple linear analysis, multiple linear analysis, determination analysis, and significance test with t test (partial), F (simultaneous) test.The results showed that the test results of the first t test hypothesis that is brand image to consumer purchase interest is tcount (10,587) > ttabel (1,984) means brand image significant effect on consumer purchase interest. Both country of origin of consumer purchase interest is tcount (8,866) > ttable (1,984) meaning there is significant influence between brand image to consumer purchase interest. F test results of brand image and country of origin of consumer purchase interest are F arithmetic (86,479) > F table (3.090). This means that the brand image and country of origin simultaneously significantly influence consumer buying interest.Keywords: Brand Image, Country Of Origin, Consumer Purchase Interest